Studi Resepsi Mahasiswa Broadcasting Universitas Mercu Buana Pada Film Journalism “Kill The Messenger” - Ahmad Ahmad Toni; Dwi Fajariko (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2017)
This study seeks to reveal receptions university student broadcasting beacon globe on film journalism. The purpose of this study to determine the meaning construction contents journalism-themed films through the movie shows them. The relations of meaning to the theme of movies they watch give you an idea about their opinions on the meanings contained in the movie scene. This study uses analysis reception Stuart Hall stated on the three main elements of meaning that is, the dominant meaning, the opposition of meaning and significance negotiations conducted by the subject studied. Construction of meaning built by the subject of research conducted with data triangulation technique, namely written questionnaires, interviews and discussions after watching the film so we get a more comprehensive picture of signification. The results showed that there are different meanings in one scene to scene ten dominated the meaning opposition to the meanings that awakened nature did the film. Next is the meaning of meaning on meaning construction negotiations in the tenth scene. Meaning become dominant meaning that does not give meaning to the subject of study of journalism movie theme. Penelitian ini berupaya untuk mengungkapkan resepsi mahasiswa broadcasting universitas mercu buana pada film jurnalistik, tujuan penelitian ini untuk mengetahui konstruksi makna isi film bertema journalism melalui tayangan film yang ditonton mereka, relasi pemaknaan dengan tema film yang mereka tonton memberikan gambaran tentang pendapat mereka pada makna-makna yang terdapat di dalam scene film. Penelitian ini menggunakan metode analisis resepsi Stuart Hall yang dinyatakan pada tiga elemen utama pemaknaan yakni, dominan makna, oposisi makna dan negosiasi makna yang dilakukan oleh subjek yang diteliti, konstruksi makna yang dibangun oleh subjek penelitian dilakukan dengan teknik triangulasi data, yakni daftar pertanyaan tertulis, wawancara dan diskusi setelah menonton film sehingga didapatkan gambaran pemaknaan yang lebih menyeluruh. Hasil penelitian menunjukan bahwa terdapat perbedaan pemaknaan pada scene satu hingga scene sepuluh yang didominasi pada pemaknaan opisisi terhadap makna-makna yang terbangun did alam film, pemaknaan berikutnya ialah pemaknaan negosiasi terhadap makna yang dibanun di dalam kesepuluh scene, pemaknaan dominan menjadi pemaknaan yang tidak memberikan arti kepada subjek penelitian terhadap tema film journalism.